Construção e validação de teste de associação implícita para preferência alimentar - Lima, Gabrielly Guimarães Barbosa (2017)
Food preferences can be understood as the result of a differentiated attention to internal and external aspects of the subject, that may constitute a mental representation about food. Dysfunctional food representations are often associated with high food intake and obesity. The approach to food preference is traditionally accomplished through self - report and evaluation of the amount of food consumption, however, the reaction time has recently been added as a way of access as a motivational indicator for eating. The Implicit Association Test (IAT) is an implicit measure that verifies the reaction time before a task of discrimination against a set of items related to different categories. The objective of this work was the construction and validation of an IAT for food preference. The sample was composed of 75 people divided into two groups, 33 obese and non-obese 42. Data collection occurred in two stages, both online and received by e-mail. In the first, the participant was asked to access the link to respond to the TAI online. At the end of Tai participant was forwarded to the link for sociodemographic questionnaire, the Impulsive Behavior Scale (Impulsive Behavior Scale - UPPS) and Food Visual Analog Scale (EAVA) of natural and processed foods. Correlations were made between the TAI and the instruments used. It was found that, both implicitly and explicitly, both groups preferred natural foods. However, there was a significant difference between the groups, indicating that the non-obese had a higher index of choice for this type of food. The findings suggest IAT as a more sensitive measure to access this preference.